NEW ASTRONOMICAL STATION ON MOUNT DUSHAK-EREKDAG. III. OBSERVATIONS OF THE roAp STAR HR 1217 - Dorokhov, N. I.; Dorokhova, T. N.; Mkrtichian, D. E. (Одеські астрономічні публікації, 2017)
Observations of well-studied roAp star HR1217 were obtained in Stromgren v-filter in single-channel mode for testing the possibilities of the dual-channel photometer. An accuracy of the single measurement is about 2.5 mmag after moving the principal periodic components from the data. Noise level in the whole frequency domain not exceed the 1 mmag.